INOVASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL QUANTUM TEACHING TERHADAP MOTIVASI BELAJAR SISWA KELAS VII DI ERA NEW NORMAL - Asnani Hayati (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2021)
The purpose of this study was to determine the effect of mathematics learning innovation using the Quantum Teaching model on students' learning motivation in the new normal era. The data used in this study are test and non-test results, where the test instruments in this study are pretest, posttest, and multiple-choice types to measure student learning outcomes. This research uses a quasi-experimental type of research. The results of the study can be concluded that the two classes, both the experimental class and the control class, all experienced an increase from the pretest results to the posttest results. However, the experimental class experienced a significant improvement process with an N-Gain score of 0.7693 in the high category compared to the control class which got an N-Gain score of 0.4803 in the medium category.